2020
DOI: 10.21203/rs.3.rs-117729/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Four Cases of Completion Lobectomy for Locally Relapsed Lung Cancer after Segmentectomy

Abstract: Background: Although completion lobectomy is the treatment of choice for local recurrence of non-small cell lung cancer after segmentectomy, few cases have been reported. We report four patients who underwent completion lobectomies for staple line recurrence after segmentectomy for stage I non-small cell lung cancer. Case presentation: Three women aged 65, 82, and 81 years underwent completion lower lobectomy after superior segmentectomy of the same lobe for local recurrence of stage I non-small cell lung canc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Notably, despite the fact that it is often recommended to open the pericardium and secure the main PA to prevent catastrophic bleeding when it is difficult to expose and divide the PA due to adhesion in the hilum, only 29% (12/41 patients) received PA taping during the CL. As previous studies have reported, completion upper lobectomy is technically tougher than completion lower lobectomy because of anatomical features, presence of adhesions around the main PA at the hilum, and effect of previous superior mediastinal nodal dissection 7 . In terms of technical issues, some authors have addressed the use of simultaneous division of the PA and lung parenchyma with a stapler to manage tight adhesions 8,9 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, despite the fact that it is often recommended to open the pericardium and secure the main PA to prevent catastrophic bleeding when it is difficult to expose and divide the PA due to adhesion in the hilum, only 29% (12/41 patients) received PA taping during the CL. As previous studies have reported, completion upper lobectomy is technically tougher than completion lower lobectomy because of anatomical features, presence of adhesions around the main PA at the hilum, and effect of previous superior mediastinal nodal dissection 7 . In terms of technical issues, some authors have addressed the use of simultaneous division of the PA and lung parenchyma with a stapler to manage tight adhesions 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…15 Only a handful of studies have reported the surgical outcomes of CL after segmentectomy. [5][6][7][8][9][10] Completion lobectomy after segmentectomy has been associated with rare adverse circumstances, including complications or local recurrences in the remaining lobe, as well as unexpected nodal involvement, which was first proposed by Omasa et al 5 In the current study, we used a similar classification for the included 41 patients. A greater percentage of complications (64%) occurred in the short interval-to-CL group, while a higher rate of local recurrence (93%) occurred in the long interval-to-CL group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations